PRE-CONTRACTUAL LIABILITY OF THE PERSON WHO TAKES POSSESSION OF ANOTHER’S PROPERTY OFFERED FOR SALE, ITS BASIS AND IMPLICATIONS دوره51 شماره4 سال1398 - ??????? ?????? , ??????? (??? ? ????)
The property which is offered for sale and possessed by buyer is terminologically called makhuz belsaum, the possessor is called akhez belsaum and the act is called akh belsaum. Delivery of property by the seller to the buyer may be considered either offer or promise to sell. The author in this paper seeks to answer the following question: what is the liability of the possessor of property with regard to property damage while in his possession? A group of jurists believe that he acts in a fiduciary capacity while the others consider him liable. Some jurists maintain that his liability is contractual while the others consider his liability as tort liability. The above said opinions have been studied through analytical-descriptive method and it has been concluded that the possessor is considered to be in a fiduciary capacity with regard to the property in his possession for testing and it is against legal logic and unjustifiable to consider liable a person who, by the owner's authorization possesses a property to test and verify and consider him as unauthorized possessor.